Nilai - Nilai Pendidikan Islam Yang Terkandung Dalam Pembacaan Kitab Al – Barzanji Pada Tradisi Pernikahan Di Desa Pematang Duku Timur - Handoyo Handoyo; Muhammad Khoiri; Muhammad Aldi Irfan (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
The tradition of reading the Al-Barzanji book is a cultural development from outside that entered Indonesia with a process brought by Sheikh Maulana Malik Ibrahim who spread Islamic teachings in the Java area by incorporating Islamic values into ancestral culture so that the process of accepting teachings that were carried out was easily accepted. In the wedding tradition of the Javanese people of Pematang Duku Timur Village, the obligation to read Al-Barzanji is carried out at night before the reception is held, the purpose of reading the Al-Barzanji book carried out by the women's majlis is to hope for blessings and smoothness in carrying out the marriage. The research method is qualitative and uses primary data and secondary data as supporting data. The values of Islamic education that are obtained are moral values, creed values, and worship values.